Chemical profile of Rhododendron luteum Sweet leaf supercritical CO2 extracts and their anti-inflammatory and antidiabetic potential - Łyko, Lena; Nowak, Renata; Olech, Marta; Gawlik, Urszula; Krajewska, Agnieszka; Kalemba, Danuta; Prokopiv, Andriy (Frontiers in Chemistry, 2025)
IntroductionTerpenes are a diverse class of natural metabolites that exhibit a range of biological activities, including antidiabetic, antiproliferative, and anti-inflammatory effects. The present study was designed to determine the chemical profile and biological activity of Rhododendron luteum leaf (RLL) supercritical CO2 (SC-CO2) extracts.Materials and methodsThe LC-APCI-MS/MS method was used to determine the composition and content of the triterpenes (including sterols). In turn, LC-ESI-MS/MS was applied for the analysis of polyphenolic compounds. The volatile composition of RLL extracts was analysed using the HS-SPME-GC-FID-MS technique. The inhibitory activity against enzymes such as xanthine oxidase (XO), lipoxygenase (LOX), hyaluronidase, α-amylase, and α-glucosidase was assessed using in vitro bioassays.Results and discussionThe LC-MS analyses revealed high levels of oleanolic acid, ursolic acid, and β-sitosterol, which belong to terpenes, as well as polyphenols such as syringic acid, ferulic acid, and p-coumaric acid, along with apigenin and its 7-glucoside. Among volatiles, the most prominent were limonene, eugenol, β-phenylethanol, and β-caryophyllene. In vitro assays showed a high hyaluronidase and moderate lipoxygenase and xanthine oxidase inhibitory activity presented by RLL supercritical extracts. Moreover, the samples were found to present α-glucosidase inhibitory activity. This may indicate the anti-inflammatory and antidiabetic potential of RLL supercritical extracts.